(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the frequency of Rheumatic manifestation inhepatitis C virus (HCV) infected patients”. Study Design: Cross sectional study Place and Duration: This study was conducted at OPD & Indoor patients of Medicine Department, Mayo Hospital, Lahore for a duration of 6 months from 28.05.2015 to 28.11.2015. Material And Methods: With approval from hospital ethical committee, 240 patients of age 20 to 60 years of either gender presenting with confirmed diagnosis of HCV diagnosed at least 6 months ago were included for the study with 95% confidence level, 6% margin of error and expected percentage of rheumatic manifestation 31% in patients. Data was entered in SPSS version 20 and analyzed through it as well. Quantitative variables like duration of HCV and age were calculated as standard deviation and mean. While qualitative variables like rheumatic manifestations such as arthritis or arthralgia, and gender were calculated as percentage and frequency. Stratification of data was done for gender, age of the patients, HCV duration and treatment taken for HCV. Post-stratification, chi-square was applied to compare stratified group. P-value≤0.05 was taken as significant. Results: The mean age of patients in the study was 40.92±12.20 years.The ratio of female to male patients was 1:2.3. 91.67% of the patients were on treatment for HCV infection and among them rheumatic manifestations were observed in 95(39.6%) of patients. Statistically, there was significant difference between the rheumatic manifestation and patients’ age i.e. p-value=0.030 Conclusion: The study thus concluded that the prevalence of rheumatic manifestation was 39.6%, arthralgia was 15.4% and arthritis was10% in patients presenting with HCV.